2016
DOI: 10.1177/0300985816646430
|View full text |Cite
|
Sign up to set email alerts
|

Canine Circovirus 1 (CaCV-1) and Canine Parvovirus 2 (CPV-2)

Abstract: Recurrent outbreaks of sudden death and bloody diarrhea were reported in March 2013 and February 2014 in a breeding colony of Papillon dogs. During the first outbreak, 1 adult dog and 2 eight-month-old puppies died. During the second outbreak, 2 ten-week-old puppies died. One puppy from the first outbreak and 2 puppies from the second outbreak were examined at necropsy. Histologically, all 3 puppies had severe segmental crypt necrosis of the small intestine and marked lymphoid follicle depletion in the spleen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 28 publications
(45 reference statements)
3
40
0
Order By: Relevance
“…The results from these findings have demonstrated that most puppies (80%; 12/15) submitted for routine autopsy were infected by two or more infectious disease pathogens. These results are similar to those described in other studies that examined one 5 , 8 , 10 , 13 , 17 , 20 , 21 , 35 or more dogs 7 , 18 , 19 , 24 , 25 , to identify infectious disease pathogens by using several diagnostic methods. The location (cytoplasmic or nuclear) for the labelling of the antigens for all infectious disease pathogens observed during this study is consistent with previous studies 26 , 36 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results from these findings have demonstrated that most puppies (80%; 12/15) submitted for routine autopsy were infected by two or more infectious disease pathogens. These results are similar to those described in other studies that examined one 5 , 8 , 10 , 13 , 17 , 20 , 21 , 35 or more dogs 7 , 18 , 19 , 24 , 25 , to identify infectious disease pathogens by using several diagnostic methods. The location (cytoplasmic or nuclear) for the labelling of the antigens for all infectious disease pathogens observed during this study is consistent with previous studies 26 , 36 .…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, recently CDV has been identified in dogs simultaneously with emerging viral infectious agents including Canine kobuvirus 22 , Canine pneumovirus 23 , and Canine respiratory coronavirus 6 , 23 . Additionally, studies have detected canine infectious disease agents due to the amplification of nucleic acids in symptomatic 6 , 23 25 and asymptomatic 19 dogs by molecular assays. Alternatively studies have combined the pattern of organ disease observed by histopathology with electron microscopy 20 , immunohistochemistry (IHC) 8 , 12 , 21 , 22 , 25 , 26 and/or the molecular identification 8 , 10 , 12 , 18 , 22 , 27 of infectious disease agents of dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with CanineCV-1, recently re-classified as ‘CanineCV’ 7 , has been associated with several disease entities accompanied by manifestations like vasculitis, hemorrhages, thrombocytopenia, neutropenia and diarrhea 2 , 7 9 , although it is also detected in healthy dogs 1 , 8 , 10 . Interestingly, dogs infected with CanineCV are often co-infected with other enteric or respiratory pathogens 2 , 7 , 10 , 11 . Therefore, the pathogenic role of CanineCV is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…DuCV infection may cause immunosuppression in ducks and the predisposed ducks are prone to be coinfected by other bacterial and viral pathogens (Soike et al, 2004;Zhang et al, 2009). The coinfection cases of parvovirus and circovirus were detected in pigs (Sun et al, 2015), canines (Anderson et al, 2017;Thaiwong, Wise, Maes, Mullaney, & Kiupel, 2016) and wild carnivores (Zaccaria et al, 2016).…”
Section: Introductionmentioning
confidence: 99%